The Relationship between Organizational Politics, Job Satisfaction and Turnover Intention in the Maritime-Related Agencies in the East Coast of Peninsular Malaysia - Mohd Yusof, J; Nur ‘Atikah Zulkiffli, S; Falindah Padlee, S; Ayuni Yusof, N (KnE Social Sciences, 2018)
The study aimed to examine the relationship between organizational politics, employee’s job satisfaction and turnover intention in the public maritime-related agencies in the east coast of Peninsular Malaysia. The study utilized cross sectional research design. An enumeration of entire population (census) was conducted on 140 employees from Royal Malaysian Custom and Department of Fisheries in Terengganu. Data for the study were collected through questionnaire. 140 set of questionnaire were distributed and 109 copies were returned. Preliminary analyses were performed to ensure violation of assumptions of normality, linearity and homogeneity which enables us to analyze the data with the aid of Statistical Package for Social Science (SPSS) and SmartPLS softwares. The findings revealed a significant association between organizational politics, employee’s job satisfaction and turnover intention. The study therefore recommended that the agencies should actively focus on positive political behaviour that will fuel workers’ job satisfaction and they should ensure proper pay structure including pay performance and other bonuses that will lead to employee job satisfaction and reduce turnover intention. Finally, the findings of this study could assist the public maritime-related agencies in the area of organizational politics that would promote employee job satisfaction. Keywords: organizational politics, job satisfaction, turnover intention